2016
DOI: 10.3389/fmicb.2016.01860
|View full text |Cite
|
Sign up to set email alerts
|

Global Antimicrobial Stewardship: A Closer Look at the Formidable Implementation Challenges

Abstract: Antimicrobial stewardship (AMS) has been touted as one of the key strategies required in tackling worldwide escalation of antibiotic resistance. Although AMS has optimized antibiotic usage and reduced the incidence of resistance development in some regions, its full global potential has been curtailed by various AMS-impeding factors. This article seeks to highlight in a detailed perspective, the key challenges that hamper global AMS endeavors, some of which include the paucity of effective implementation strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 22 publications
2
35
0
Order By: Relevance
“…A study from developed countries also showed similar findings, as health practitioners reported having a limited knowledge of the local resistance patterns and viewed antibiotic resistance to be less of a problem locally than nationally . It is important to note that the use of antibiotics without adequate knowledge on local resistance patterns could contribute to irrational antibiotic use, treatment failure and increased spread of antibiotic resistance . Although infectious diseases are more common in developing countries, thus possibly leading to the more use of antibiotics compared to developed countries, the diagnoses and rationale to use antibiotics are often clinically based, with minimal laboratory investigations .…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…A study from developed countries also showed similar findings, as health practitioners reported having a limited knowledge of the local resistance patterns and viewed antibiotic resistance to be less of a problem locally than nationally . It is important to note that the use of antibiotics without adequate knowledge on local resistance patterns could contribute to irrational antibiotic use, treatment failure and increased spread of antibiotic resistance . Although infectious diseases are more common in developing countries, thus possibly leading to the more use of antibiotics compared to developed countries, the diagnoses and rationale to use antibiotics are often clinically based, with minimal laboratory investigations .…”
Section: Discussionmentioning
confidence: 77%
“…Thus, culture‐guided management of infectious diseases, as well as availability of experts in the area of infectious disease, would increase diagnostic certainty, a more rational antibiotic use, and save cost . Such efforts to streamline the use of antibiotics to promote a more rational approach are less common in developing countries when compared to developed countries …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was however noteworthy that the 3 rd highest contribution to medication dispensed was antiinfective for short-term use, comprising 15 % of all medications prescribed. Considering that this study did not capture antiinfective dispensed by the physicians themselves, it is likely this is an underestimation of the true rate of antibiotic prescribing and raises the question regarding the appropriateness of antibiotic prescribing at a time where resistance continues to a major point of concern [14,15] . Indeed, it has been shown that prohibiting physicians from dispensing significantly reduces inappropriate prescriptions of antibiotics [16] .…”
mentioning
confidence: 99%